PRIMARY MULTIPLE TUMOR EPIDEMIOLOGY - Mamadalieva, Ya.S.; Abdukarimov, U.G. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
When an a patient more than one tumor in the same or another organ suggests that primary multiple tumors may be present. For epidemiological studies, different concepts of multiple tumors are used with two main definitions taken from the International Association of Cancer Registries and the International Agency for Research on Cancer. The differences in these two definitions should be taken into account when analyzing reports for several key criteria. This article discusses and summarizes some of the literature data on In general, the frequency of multiply primary tumors ranges from 2-17%. The reasons that can predispose patients to the primary multiple tumors can be grouped into factors related to the person himself, lifestyle and the influence of environmental conditions. General principles and possible treatment options for patients with synchronous and metachronic primary multiple malignant tumors are highlighted.